Double Burden (Dual Roles) of Women in Domestic and Public: Perspectives Surah Al-Qasas 23 and Surah Al-Ahzab 33 - Halimah, Ulfatul (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The term "Double Burden" refers to a situation in which women simultaneously hold two or more roles as wives, mothers, and employees outside the house, alongside their traditional roles within the household. In this framework, a conflict arises between family responsibilities and employment, creating a dilemma faced by many working women. In Islam, there are various perspectives on the roles of women, including whether they should work outside the house or focus more on domestic duties. This article discusses the two roles performed by women, both in the domestic and public spheres. There are two Quranic verses that indicate different point of views: Surah Al-Qasas: 23 demonstrates women's ability to work outside the home, while Surah Al-Ahzab: 33 suggests that women are better off engaging in activities within the home. The result is the domestic and public roles can both function with the commitment between partners and in accordance with their respective abilities to fulfill their responsibilities.